2018
DOI: 10.1007/jhep12(2018)028
|View full text |Cite
|
Sign up to set email alerts
|

AdS2 holography: mind the cap

Abstract: AdS 2 plays an extremely important role in black-hole physics. We construct several infinite families of supergravity solutions that are asymptotically AdS 2 in the UV, and terminate in the IR with a cap that is singular in two dimensions but smooth in ten dimensions. These solutions break conformal invariance, and should correspond to supersymmetric ground states of a holographically dual CFT 1 . We solve the free massless scalar wave equation on a family of these solutions, finding towers of finite-energy no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
120
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(129 citation statements)
references
References 119 publications
(206 reference statements)
9
120
0
Order By: Relevance
“…The volume V 4 / 4 str of the compactification is bounded by n 1 /n 5 in order for the F1-NS5 description to be valid; beyond that, the valid weakly-coupled effective description switches to the S-dual D1-D5 frame (see for instance [133]). Indeed we see that the W-string becomes lighter 22 Additionally the W-brane can wrap around T 4 as it winds along the supertube helix; or it can wrap only the T 4 . In the AdS 3 limit R −1 y = Rỹ → 0, the brane wrapping only the supertube helix is lightest.…”
Section: W-brane Excitationsmentioning
confidence: 92%
“…The volume V 4 / 4 str of the compactification is bounded by n 1 /n 5 in order for the F1-NS5 description to be valid; beyond that, the valid weakly-coupled effective description switches to the S-dual D1-D5 frame (see for instance [133]). Indeed we see that the W-string becomes lighter 22 Additionally the W-brane can wrap around T 4 as it winds along the supertube helix; or it can wrap only the T 4 . In the AdS 3 limit R −1 y = Rỹ → 0, the brane wrapping only the supertube helix is lightest.…”
Section: W-brane Excitationsmentioning
confidence: 92%
“…However, the existence of a capped AdS 2 does not contradict with the no-go theorem, because the divergent dilaton is interpreted as the collapsing of an internal S 1 which caps off the geometry. In [84], it was found that the non-supersymmetric excitations at the bottom of the capped AdS 2 superstratum are normalizable with spectrum ∆E = 4J R /(N R y ), 28 which for J R = 1/2 reproduces the CFT expectation. However, it remains to be seen if these excitations preserve the AdS 2 28 The spectrum in the (1, 0, n) geometry was studied in [83] before.…”
Section: Further Aspects Of Superstratamentioning
confidence: 93%
“…At r ∼ a, there is a momentum wave that supports the geometry which smoothly caps off at r = 0. For studies of various physical aspects of this solution, see [42,44,79,[82][83][84][85][86][87][88][89][90], some of which are reviewed in section 5.…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In some classes of these geometries, the massless scalar wave equation is even separable [4,[7][8][9]. This has enabled a great deal of analysis of such geometries and an investigation of their possible effects on microstructure [4,10,11,6,7].…”
Section: Introductionmentioning
confidence: 99%